MEDAN MAKNA DALAM PEMEROLEHAN LEKSIKON AWAL ANAK USIA DUA TAHUN: KAJIAN PSIKOLINGUISTIK - Syamsul Rijal (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the characteristics of the meaning field in language acquisition in two-year-old children from a psycholinguistic perspective. The method used was a qualitative descriptive method with naturalistic observation and utterance recording techniques. Analysis was conducted by identifying semantic relations among referents in each central word that constitutes the semantic field. The research focuses on how children construct lexical meaning through referential expansion that forms an initial network of meanings. The data consists of utterances from a two-year-old child demonstrating the use of a single word to refer to several different objects or events that nevertheless belong to one domain of conceptual experience. Analysis was conducted by identifying semantic relations among referents in each central word that constitutes the semantic field. The results show that the child’s early lexicon is not organized taxonomically like the adult lexical system, but is instead based on a network of conceptual meanings. Semantic fields are formed through four main principles: prototype, perceptual similarity, functional relations, and event schema. These findings indicate that meaning acquisition in two-year-old children is a process of conceptual categorization, in which a single lexical form functions as the center of representation for a wide range of experiences before more detailed semantic differentiation occurs.